Appraisal of endometrial sampling and clinic-radio-pathological correlation: Analysis of 153 cases - Atul Beniwal; Priyanka Dahiya; Heena Pradeep Shah; Upender Sharma (Wolters Kluwer Medknow Publications, 2023)
Background: Endometrial sampling is a safe and effective diagnostic procedure in evaluation of abnormal uterine bleeding (AUB), infertility cases, and in studying response of endometrium to various therapies. This study was directed to analyze the clinico-radio-pathological spectrum of endometrial samples in these cases as well as to classify various lesions of endometrium. Methodology: A prospective cross-sectional study over 2-year duration was carried out in a tertiary care center, and a total of 153 endometrial samples received in the department of pathology, meeting inclusion criteria, were included. Clinical details were obtained from the patient case files. A systematic approach was followed to process the samples and checklist was used for reporting the endometrial biopsy. Results: Heavy menstrual bleeding (29.4%) was the most common clinical presentation in cases of AUB. Precursor lesions were the most common diagnosis on histopathology (23.7%), followed by normal physiological endometrium (21.7%). More than 50% of cases of infertility had no specific pathology in the endometrium. Conclusions: Owing to an underlying pathology, endometrium demonstrates varied patterns of disease spectrum. Each diagnostic modality has its own limitations and advantages. Hence, clinic-radio-pathological is essential for correctly diagnosing an endometrial pathology.